PESO AO NASCER EM CRIANÇAS INDÍGENAS E FATORES ASSOCIADOS: ESTUDO TRANSVERSAL EM COORTE DE NASCIMENTOS INDÍGENAS EM MATO GROSSO DO SUL - SUELEN ROTELA DOS REIS (2024)
Birth weight is an important indicator of morbidity, mortality, and health outcomes in both childhood and adulthood. This study aimed to investigate birth weight and associated factors in Indigenous children from an Indigenous birth cohort in Mato Grosso do Sul, Brazil. This is a cross-sectional study based on the baseline data of an Indigenous birth cohort conducted with 242 live births in 13 hospitals across ten municipalities in the state (Antônio João, Amambai, Aquidauana, Caarapó, Iguatemi, Dourados, Miranda, Sidrolândia, Tacuru, and Campo Grande) from November 21, 2021, to August 24, 2022. Birth weight was considered the outcome variable, while demographic, socioeconomic, and health-related variables were considered exposure variables. Maternal anthropometric data were collected to classify nutritional status and gestational weight gain, in addition to sociodemographic, economic, reproductive, and obstetric history of the mother, as well as newborn weight, through interviews with mothers and review of records from the Maternal Health Booklet and hospital records. A multiple linear regression model was applied to determine factors significantly associated with mean birth weight. The mean birth weight of Indigenous children was 3,198 g. Bivariate analysis showed a significantly higher mean birth weight in children of mothers in the second tertile of asset ownership, mothers with pregestational overweight, and mothers with excessive gestational weight gain. Lower mean birth weights were observed in children of Guarani and Kaiowá ethnicities, children born in the southern region of the state, children of mothers who consumed alcohol during pregnancy, and children of mothers living in households with water collection points outside the domicile. In adjusted analyses, birth weight was significantly higher among children of women with pregestational overweight. Additionally, residing in the southern region of the state and having a water tap outside the domicile were statistically associated with lower birth weight among Indigenous children. The birth weight of Indigenous children in Mato Grosso do Sul is associated with maternal nutritional status and socio-environmental characteristics. The study highlights the need to improve nutritional surveillance among Indigenous women of childbearing age and reaffirms its relevance in supporting the SASI-SUS (Sistema de Atenção à Saúde Indígena do SUS) in the development of intersectoral public policies that ensure access to potable water to reduce ethnic-racial health inequalities.